Association of Renal and Bladder Ultrasonography Findings with Urinary Tract Infection Recurrence, High-Grade Vesicoureteral Reflux, and Renal Scarring - Hye Won Park; Hyeil Jin; Su Jin Jeong; Jun Ho Lee (Korean Society of Pediatric Nephrology, 2015)
Introduction: This study investigated whether renal and bladder ultrasonography (RBUS) findings performed in children with the first incidence of febrile urinary tract infection (UTI) can predict UTI recurrence, high-grade vesicoureteral reflux (high-grade VUR), or acquired renal scarring (aRS). Methods: In all, 917 children who were admitted to our hospital from January 2001 to October 2010, owing to the first incidence of febrile UTI were enrolled in this study. All children underwent RBUS during admission. The mean follow-up was 7.9 months (standard deviation [SD]±13.3). UTI recurrence rates were calculated according to various clinical parameters. By using bivariate and multiple logistic regression analyses, we determined whether age, sex, abnormal RBUS findings, abnormal dimercaptosuccinic acid renal scan findings, or RBUS findings parameters were predictive of UTI recurrence, high-grade VUR, or aRS. Results: On RBUS, hydronephrosis and congenital anomaly of the kidney and urinary tract significantly predicted UTI recurrence. A small kidney, hydroureter, hydronephrosis, cortical thinning, and increased parenchymal echogenicity significantly predicted high-grade VUR. However, their odds ratios (OR) are low compared to normal RBUS findings (recurrent UTI: OR 0.432 and 0.354 vs. 0.934, respectively, high-grade VUR: .019, 0.329, 0.126, 0.058, and 0.188 vs. 2.082, respectively). No RBUS findings significantly predicted aRS. Recurrent UTI, high-grade VUR, and abnormal RBUS findings significantly predicted aRS (OR of 4.80, 4.61, and 2.58, respectively). Conclusion: RBUS is necessary to exclude severe congenital renal scarring, obstructive uropathy, and renal abscess at the first incidence of febrile UTI and is helpful in determining the need for subsequent clinical imaging.